2020
DOI: 10.3390/molecules25051180
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiproliferative Screening Of Novel Analogs of Regioselectively Demethylated Colchicine and Thiocolchicine

Abstract: Colchicine, a pseudoalkaloid isolated from Colchicum autumnale, has been identified as a potent anticancer agent because of its strong antimitotic activity. It was shown that colchicine modifications by regioselective demethylation affected its biological properties. For demethylated colchicine analogs, 10-demethylcolchicine (colchiceine, 1) and 1-demethylthiocolchicine (3), a series of 12 colchicine derivatives including 5 novel esters (2b–c and 4b–d) and 4 carbonates (2e–f and 4e–f) were synthesized. The ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…More to the point, there was no significant difference in the BE values among these metabolites, although they had different interaction forces and the hydrogen bonding sites for complexing. These results provided additional evidence for the structure-toxicity relationship of COL analogues from a new viewpoint and were in good agreement with those cell/animal-based experimental observations previously reported [12,32]. Further, considering the fact that COL in vivo is apt to form more readily excreted metabolites, the findings from the present study thus clearly demonstrated that metabolic transformation through phase I demethylation and phase II conjugation with hydrophilic moieties would lead to in vivo detoxification for COL.…”
Section: Nosupporting
confidence: 91%
See 1 more Smart Citation
“…More to the point, there was no significant difference in the BE values among these metabolites, although they had different interaction forces and the hydrogen bonding sites for complexing. These results provided additional evidence for the structure-toxicity relationship of COL analogues from a new viewpoint and were in good agreement with those cell/animal-based experimental observations previously reported [12,32]. Further, considering the fact that COL in vivo is apt to form more readily excreted metabolites, the findings from the present study thus clearly demonstrated that metabolic transformation through phase I demethylation and phase II conjugation with hydrophilic moieties would lead to in vivo detoxification for COL.…”
Section: Nosupporting
confidence: 91%
“…These demethylated compounds are prone to further phase II conjugation with hydrophilic moieties (i.e., glucuronate, sulfate, and glutathione) to form more readily excreted metabolites [ 30 , 31 ]. A variety of studies have also demonstrated the great changes in bioactivities of COL caused by metabolic transformation [ 32 ]. For example, COL can induce a sharp increase in the level of serum transaminases such as AST and ALT, on which the demethylated metabolites 2/3/10-DMC under the same conditions have little influence, suggesting reduced liver toxicity of COL along with metabolism [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Replacement of the C-1 methoxy group of colchicine by other alkyloxy or acyloxy groups did not lead to significant changes in the cytotoxicity of the compounds; however, bulky substituents led to reduced activity (Scheme ). The same held true for a C-1-modified thiocolchicine …”
Section: Ring a Modificationsmentioning
confidence: 99%
“…Secondly, the presence of a methoxy group on the quinolone ring also adds to the efficacy of CTRs. It is known that methoxy groups are present in colchicine, and are necessary for its tubulin binding activity 31 and thus its anti-proliferative activity 32 . Our finding is consistent with this previous finding.…”
Section: Discussionmentioning
confidence: 99%